(untitled) - Miller, Michael (San Francisco, 2002)
Have you ever engaged in high-risk Internet activities? You have if you've ever shopped, chatted with a friend, played a game or swapped an MP3 file while online. And you'll be shocked to learn how incredibly vulnerable your PC is if you're connecting via cable/DSL. Your risk of Internet attacks is likely to increase in the coming years--in both frequency and destructiveness. It's simply becoming easier for computer criminals to access and sabotage your PC, and even to steal your identity. Learn how to protect your PC from fast-spreading viruses in disguise, Internet-connection hijackers, con artists after your personal information, annoying spam e-mail and relentless pop-up advertising. Absolute PC Security and Privacy shows you how to detect security holes, reduce your chances of attack, recognize when you're under attack and stop an attack in progress.
Keywords: Computer security,Computer networks,Internet,Bảo mật máy tính,Mạnh máy tính,Internet; Security measures,Security measures,Các biện pháp an ninh,Các biện pháp an ninh